1974
DOI: 10.1111/j.1471-0528.1974.tb00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Anaemia During Pregnancy a Comparative Study of Two Socio‐economic Classes

Abstract: Summary The incidence of haemoglobin and nutrient deficiencies during pregnancy was studied in 88 women of poor economic background and 88 from the middle economic class. Blood samples were taken in the first trimester before treatment, and after treatment either with iron, or iron plus folic acid. In the first trimester, the poor class patients had a statistically significantly higher rate of deficiency in all parameters except serum folate and total iron‐binding capacity (TIBC). At term, despite being treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This finding is in agreement with those of Akanmu et al (1998), Ogbede et al (1994), Lamina and Sorunmu (2003) and Molina et al (1974). This was not unexpected as many investigators have observed adverse outcomes of health status, including anaemia in association with low socioeconomic class (Molina et al 1974).…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with those of Akanmu et al (1998), Ogbede et al (1994), Lamina and Sorunmu (2003) and Molina et al (1974). This was not unexpected as many investigators have observed adverse outcomes of health status, including anaemia in association with low socioeconomic class (Molina et al 1974).…”
Section: Discussionsupporting
confidence: 94%
“…About half the pregnant women in our study were iron deficient and 22.7% had iron-deficiency anaemia. This prevalence is high, and is at variance with reports from India and Turkey [10][11][12][13]. In a study in Istanbul and Izmit the prevalence of iron deficiency in pregnant women was 52.3% [10].…”
Section: Discussionmentioning
confidence: 89%
“…Shukla et al studied 246 pregnant and non-pregnant women in 7 vil-lages in India and showed prevalence of anaemia to be between 25% and 68% [12]. Molina et al studied 88 pregnant women of lower and middle economic status and found significantly lower ferritin and Hb levels in the poorer group [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s, 2 groups reported the lack of association of folate deficiency with preeclampsia (hypertension and proteinuria) or pregnancy-induced hypertension (144,145). In the 1990s, research interest intensified on the premise that placental vasculopathy secondary to hyperhomocysteinemia may be the underlying cause of preeclampsia (77, 137-139, 141, 146 -163).…”
Section: Preeclampsiamentioning
confidence: 99%